Penurunan Pendapatan Pedagang Pasar Pondok Labu, Dampak Munculnya Marketplace - Putra, Candra Galang Gemilang; Hanif Arkan, Muhammad; Shanti Levianita, Maulvina; Kadafi, Alifio; Putri Lapian, Nesia; Azzahra, Ulfia; Azhari Syah Putra, Zidhan; Hizkia Nathanael, Kevin; Akbar Hakim, Muhammad; Siti Karaniya, Avishtya (Peneliti.net, 2024)
This study shows that there is a significant impact on the income of traders in Pondok Labu Market, South Jakarta, Indonesia due to technological developments and rapid online market penetration. Key influencing factors include more competitive prices on online platforms, promotions by celebrities and influencers, and the superior convenience of online shopping. The government's response to this decline was to take tough action to close Tiktok Shop. In a traditional and conventional market context, this study used a qualitative Grounded Theory Design approach involving 15 sources and several respondents. Questionnaire results highlight seller perceptions of falling revenue, while potential solutions include more effective marketing strategies, product innovation, and collaboration between traditional and online marketplaces. Through its contributions, this research plays a vital role in supporting local traders, shaping government policy and understanding the economic and social impacts arising from technological change. This research therefore makes a valuable contribution to maintaining the sustainability of traditional markets in the digital age.